Investigating the effects of explicit oral communication strategy training of ESL learners at higher institution : a multilingual context. - Mohd. Ramli, Nur Aziera (2011)

(untitled)
The study is justified on the following grounds: First, the issue of teaching communication strategies has been controversial over the past few decades. Some studies questioned the teachability of communication strategies. Therefore, this study aims to offer some understanding of the relationship between communication strategy instruction, the ESL learners’ strategy used, their task performance and attitudes towards the communication strategy training.